Zur Geschichte des Schriftrussischen Privatkorrespondenz des 17. und fruehen 18. Jahrhundert - Kretschmer, Anna (Specimina philologiae Slavicae, 1998)
The series Specimina philologiae Slavicae, founded in 1972 by the Frankfurt Slavists Olexa Horbatsch and Gerd Freidhof, is today performed by Holger Kuße (Dresden), Peter Kosta (Potsdam), Beatrix Kreß (Hildesheim), Franz Schindler (casting), Barbara Sonnenhauser (Zurich) and Nadine Thielemann (Vienna) issue. The series includes monographs, anthologies and textbooks covering all areas of Slavic, Linguistics, Literary and Cultural Studies. In linguistics, both linguistic and innovative works on pragmatics and semantics, slavic minor languages ​​and discourse linguistics are published. In literary and cultural studies, one of the areas of special interest is Russian philosophy.